Funding Inequities in New Hampshire School Districts: Political Realities and Public Attitudes - Virginia E. Garland (Journal of Research in Rural Education, 1991)
Equity has a central role in recent research on rural school finance policy, especially in the analysis of the effects of disparities in district funding on educational opportunity. Fiscal inequities have led to recent major tax reform efforts throughout the nation, in states such as Texas, Kentucky and Tenessee. An appropiate and current state case study of inequality is New Hamshire, where a primarly rural public school system is funded by regressive property taxes and lottery revenues. Although there is a wide spread in pupil expenditures between rich and poor schools in New Hamshire, with none of the ten poorest districts offering kindergarten, the existing funding plans has not been restructured by the politically conservative state legislature. Despite the commitment of most state legislature. Despite the commitment of most states legislators to "the pledge" of no new taxes, the result of a recent survey of over 500 New Hamshire citizens indicates that the public support equalized funding efforts through the raising of broadbased state income or sales taxes.